2009
DOI: 10.1074/jbc.m109.028266
|View full text |Cite
|
Sign up to set email alerts
|

A PH Domain in the Arf GTPase-activating Protein (GAP) ARAP1 Binds Phosphatidylinositol 3,4,5-Trisphosphate and Regulates Arf GAP Activity Independently of Recruitment to the Plasma Membranes

Abstract: ARAP1 is a phosphatidylinositol 3,4,5-trisphosphate (PtdIns-(3,4,5)P 3 )-dependent Arf GTPase-activating protein (GAP) with five PH domains that regulates endocytic trafficking of the epidermal growth factor receptor (EGFR). Two tandem PH domains are immediately N-terminal of the Arf GAP domain, and one of these fits the consensus sequence for PtdIns(3,4,5)P 3 binding. Here, we tested the hypothesis that PtdIns(3,4,5)P 3 -dependent recruitment mediated by the first PH domain of ARAP1 regulates the in vivo and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 58 publications
1
34
0
Order By: Relevance
“…Another possibility for the regulation of ARAP1 activation via Tyr 231 phosphorylation is through a change of localization of ARAP1. Campa et al (43) has shown that ARAP1 is recruited to the plasma membrane independent of phosphatidylinositol (3,4,5)-triphosphate (PIP 3 ) and that subsequent production of PIP 3 triggers Arf-GAP activity. Thus, we presume that ARAP1 might be phosphorylated by and recruited to PTK6 at the plasma membrane through its SH2 domain, prior to activation of Arf-GAP through the contact of its nearby PH domain with membrane PIP 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility for the regulation of ARAP1 activation via Tyr 231 phosphorylation is through a change of localization of ARAP1. Campa et al (43) has shown that ARAP1 is recruited to the plasma membrane independent of phosphatidylinositol (3,4,5)-triphosphate (PIP 3 ) and that subsequent production of PIP 3 triggers Arf-GAP activity. Thus, we presume that ARAP1 might be phosphorylated by and recruited to PTK6 at the plasma membrane through its SH2 domain, prior to activation of Arf-GAP through the contact of its nearby PH domain with membrane PIP 3 .…”
Section: Discussionmentioning
confidence: 99%
“…ARAP1 is reported to be an Arf-GAP that preferentially uses Arf5, but can also use Arf1 and Arf6 (30,(43)(44). Arf6 has been implicated in multiple pathways of endocytosis (45).…”
Section: Discussionmentioning
confidence: 99%
“…Large unilamellar vesicles (LUVs) containing various phospholipids were prepared by extrusion with lipids purchased from Avanti Polar Lipids and Echelon Biosciences as described previously (16). They contained molar ratios of 40% phosphatidylcholine, 25% phosphatidylethanolamine, 15% phosphatidylserine, 10% cholesterol, and 10% phosphatidylinositol (PI), or 9.5% PI plus 0.5% of various phosphatidylinositol phosphate (PIP), including PI 3-phosphate, PI 4-phosphate, PI 5-phosphate, PI 3,4-bisphosphate, PI 3,5-bisphosphate, PI(4,5)P 2 , and PI 3,4,5-trisphosphate.…”
Section: Methodsmentioning
confidence: 99%
“…76,77 All 4 subtypes of Arf GAPs may be allosterically regulated. 23,54,76,78 ASAP1 has been the most extensively examined Arf GAP and will be discussed here.…”
Section: Introductionmentioning
confidence: 99%
“…53 For the Arf GAPs examined, the PH domains do not have a role in membrane recruitment, but are critical for activity and for regulation of activity. 54,55 Cooperative binding of ligands controls activity of the Arf GAP ASAP1. 23 Figure 2.…”
Section: Introductionmentioning
confidence: 99%